Planning and designing large energy systems with a special emphasis on their impact on the environment - Luburić, Veselin D.; Bakrač, Saša T.; Milanović, Miško M. (Vojnotehnički glasnik / Military Technical Courier, 2014)
This paper analyzes the impact of planning and designing large power systems on the environment, such as the DSP 400 kV optical cable from the Montenegrin coast to Pljevlja. It is a very complex and multidisciplinary project, and involves the analysis of a number of important factors and cause-effect relationships that such a system can produce. The analysis was guided by the fact that this is an atypical example, from the planned and implemented aspect unknown both on the national and wider regional level. For this reason, it is challenging to shed light on the consequences of any such system and structure, which is specific in many ways, and whose repercussions in the near future are still vague. The paper discussed European and international experiences as well as their perceptions of problems with similar solutions in practice.